Incidence of posterior vessel wall puncture during ultrasound guided vascular access: Short axis versus long axis approach - Niraj Kumar; Ashish Bindra; Gyaninder Pal Singh; Keshav Goyal; Arvind Chaturvedi; Naveen Yadav; Arun Kumar Yadav (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Posterior vessel wall puncture (PVWP) is a common complication of ultrasound (US) guided central venous cannulation. We evaluated and compared the frequency of PWVP of internal jugular vein using short axis (SA) and long axis (LA) approach of US-guided needle cannulation. As a secondary objective incidence of carotid puncture was assessed. Material and Methods: Prospective, single-blinded, cross over, observational study at Urban Level I Neuroanesthesiology and Critical Care Department. Residents receiving standard education on ultrasound-guided central venous cannulation were asked to place an US-guided catheter using either short axis or long axis approach on a human torso mannequin. During the procedure, the path of the needle was carefully observed by the investigator for any PVWP and carotid puncture without interference with the placement procedure. The confidence level of the resident for the intraluminal placement of the needle tip was measured on a 10-point Likert scale. Results: Forty residents participated in the study. The incidence of PVWP in SA and LA group was 40% and 17.5% respectively and was statistically significant (p = 0.026). There was no incidence of carotid artery puncture in either of the group. The mean confidence of intraluminal placement of needle was significantly higher in the LA group (8.32) as compared to the SA group (5.95). Conclusion: Lower incidence of PVWP was seen in LA as compared to the SA approach during US-guided IJV cannulation in phantom in residents having previous experience of CVC (central venous cannulation) in landmark technique only. Participants were more confident about intraluminal needle placement in the LA group compared to the SA group.